2022
DOI: 10.1038/s41467-022-33449-9
|View full text |Cite
|
Sign up to set email alerts
|

Nano-electromechanical spatial light modulator enabled by asymmetric resonant dielectric metasurfaces

Abstract: Spatial light modulators (SLMs) play essential roles in various free-space optical technologies, offering spatio-temporal control of amplitude, phase, or polarization of light. Beyond conventional SLMs based on liquid crystals or microelectromechanical systems, active metasurfaces are considered as promising SLM platforms because they could simultaneously provide high-speed and small pixel size. However, the active metasurfaces reported so far have achieved either limited phase modulation or low efficiency. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The progress on the metasurface optics has emerged as an influential platform in the field of diffractive optics, with the benefits of compactness and their high control capacities to modulate electromagnetic waves (3)(4)(5)(6)(7). These advantageous features open up avenues for expanding functionalities of optical elements and miniaturizing optical systems, as demonstrated in various applications, such as metalenses (8)(9)(10)(11)(12)(13)(14)(15)(16)(17), holograms (18)(19)(20), deflector (3,(21)(22)(23)(24), color filters (25), optical computation (26), phase imaging (27,28), polarization imaging (29,30), hyperspectral imaging (31), and active devices (32,33). The use of metasurface and volumetric meta-optics has allowed for the development of color router devices that can split and focus the incident visible light to a designated photodiode instead of simply filtering out colors (34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%
“…The progress on the metasurface optics has emerged as an influential platform in the field of diffractive optics, with the benefits of compactness and their high control capacities to modulate electromagnetic waves (3)(4)(5)(6)(7). These advantageous features open up avenues for expanding functionalities of optical elements and miniaturizing optical systems, as demonstrated in various applications, such as metalenses (8)(9)(10)(11)(12)(13)(14)(15)(16)(17), holograms (18)(19)(20), deflector (3,(21)(22)(23)(24), color filters (25), optical computation (26), phase imaging (27,28), polarization imaging (29,30), hyperspectral imaging (31), and active devices (32,33). The use of metasurface and volumetric meta-optics has allowed for the development of color router devices that can split and focus the incident visible light to a designated photodiode instead of simply filtering out colors (34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%
“…One approach is active depth-detection that employs a light source to illuminate a target object and requires many optical components, which hinders the miniaturization process. The second method is passive depth detection, which acquires depth information in the presence of ambient light, thereby reducing the size to some extent. Therefore, further compressing the optical components is vital to minimize the footprint of the passive depth-detection systems. Metasurfaces, as two-dimentional metamaterials, offer a potent and lightweight platform for light manipulation. Moreover, metalenses, which are primarily employed in imaging, exhibit remarkable functionalities. Numerous single-lens cameras based on metalenses have been developed for compact integration. Specifically, some studies have demonstrated that metalenses based on two interleaved off-axis focal spots or a DH-PSF exhibit superior accuracy in depth recovery for single-lens passive depth detection. As diffractive optical elements, the metalenses used for depth detection suffer from significant chromatic aberrations. Therefore, the incorporation of filters is essential for obtaining narrowband light.…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials containing artificial structures can give rise to curious wave properties in the design waveband by manipulating its structure and compositions [11][12][13][14] . Optical resonators with asymmetric structures can excite polarization selectivity response [15][16][17][18] . Polarization sensitive metamaterial absorber can realize polarization selective absorption for incident radiation [19][20][21] , and has the advantages of small volume and easy integration 22,23 .…”
Section: Introductionmentioning
confidence: 99%